2008
DOI: 10.1186/1751-0759-2-20
|View full text |Cite
|
Sign up to set email alerts
|

Changes in salivary physiological stress markers induced by muscle stretching in patients with irritable bowel syndrome

Abstract: Background: Psychophysiological processing has been reported to play a crucial role in irritable bowel syndrome (IBS) but there has been no report on modulation of the stress marker chromogranin A (CgA) resulting from muscle stretching. We hypothesized that abdominal muscle stretching as a passive operation would have a beneficial effect on a biochemical index of the activity of the sympathetic/adrenomedullary system (salivary CgA) and anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
2
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 53 publications
0
15
2
1
Order By: Relevance
“…It was reported that CgA, which is a catecholamine derivative, could be used to evaluate stress and pain levels. Despite the these results obtained in our study, a review of the literature showed that CgA levels had been found to increase quantitatively in painful, and stressful conditions [8][9][10]. In a study by Toda et al [26], students were assigned 10 min sequential arithmetic tasks and it was found that they had increased serum CgA levels.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…It was reported that CgA, which is a catecholamine derivative, could be used to evaluate stress and pain levels. Despite the these results obtained in our study, a review of the literature showed that CgA levels had been found to increase quantitatively in painful, and stressful conditions [8][9][10]. In a study by Toda et al [26], students were assigned 10 min sequential arithmetic tasks and it was found that they had increased serum CgA levels.…”
Section: Discussioncontrasting
confidence: 84%
“…Stress activates the hypothalamic-pituitary-adrenal axis [25]. The activity of the HPA and sympatho-adrenal systems (S/A) can be evaluated by measuring the cortisol and catecholamine levels in the blood and sputum [8]. In sputum samples of patients referred to ERs because of toothaches, it was found that the cortisol levels increased in parallel to the severity of the pain experienced by the patient [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The biological mechanism involves the autonomous nervous system (ANS) which, when stimulated by adrenergic receptors, leads to secretion of catecholamines (adrenalin/noradrenalin) (CAs), neuropeptides such as substance P (SP) [18] and chromogranin A (CgA) by the adrenal medulla, thereby indirectly provoking periodontal tissue breakdown. Catecholamines regulate the immune response by stimulation of immune cell propagation and activity [19,20], whereas CgA have antimicrobial effects [21]. The autonomous nervous system acts on the salivary glands during stress by secreting enzymes such as salivary alpha-amylase (sAA), which acts by neutralizing and preventing pathogens from entering the body via the mucosal surfaces and inhibiting the adherence and growth of bacteria in the oral cavity [22,23].…”
Section: Introductionmentioning
confidence: 99%